2014
DOI: 10.19171/uuefd.19923
|View full text |Cite
|
Sign up to set email alerts
|

Topluma Hizmet Uygulamaları Dersinin Toplumsal Bilinç Kazandırmadaki Etkisi

Abstract: Bu araştırma, bir öğretmende olması gereken toplumla bütünleşme, toplumsal liderlik, toplumsal sorumluluk gibi birtakım özellikleri kazandırmada THU dersinin önemi ve gerekliliği konusunda öğretmen adaylarının görüşlerini ortaya çıkarmak amacıyla yapılmıştır. Nitel araştırma yöntemi kullanılarak hazırlanan bu çalışmanın araştırma grubunu Samsun Ondokuz Mayıs Üniversitesi Eğitim Fakültesi ve Marmara Üniversitesi Atatürk Eğitim Fakültesi'ndeki 16 Sosyal Bilgiler öğretmen adayı oluşturmuştur. Araştırmanın sonunda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 13 publications
0
3
0
2
Order By: Relevance
“…Research reveals that community service practices increase social awareness. Kesten, Köçer and Egüz (2016) found that community service practices are very important in terms of raising social awareness in their study called "The Effect of Community Service Practices Course on Raising Social Awareness". The fact that 58 studies in the field of Community Service Practices show that community service practices are given great importance (Noyan & Kesten, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Research reveals that community service practices increase social awareness. Kesten, Köçer and Egüz (2016) found that community service practices are very important in terms of raising social awareness in their study called "The Effect of Community Service Practices Course on Raising Social Awareness". The fact that 58 studies in the field of Community Service Practices show that community service practices are given great importance (Noyan & Kesten, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Buna göre, sosyal duyarlılık dersi kapsamında gerçekleştirilen sosyal sorumluluk projesi uygulamaları öğrencilerin kültürlerarası duyarlılık değerini kazanmaları ya da geliştirmelerinde istatistiksel olarak anlamlı bir etkiye sahip değildir. Alan yazındaki çalışmalarda topluma hizmet uygulamaları dersini alan öğrencilerin toplumsal sorunlara ve çevreye duyarlılık kazandıkları dikkat çekmektedir (Gökçe, 2011, Kesten, Köçer ve Egüz, 2014Nas ve ark., 2015). Kültürlerarası duyarlılık, bireyin içinde yaşadığı toplumdaki kültürel farklılıkları ayırt etme (Hammer, 2015), anlama ve takdir etmede olumlu ve istekli bir tutum geliştirebilmesini anlatmakta (Chen ve Starosta, 2000), bu da farklı kültürlerden insanlarla iletişime geçmeyi gerektirmektedir.…”
Section: Tartışma Ve Sonuçunclassified
“…In addition, it was determined that CSP course made significant contributions to the development of skills related directly to democratic attitudes and values such as social sensitivity, responsibility, communication, teamwork, problem solving, and participation in non-governmental organizations (Özdemir and Tokcan, 2010;Waldstein and Reiher, 2001;Yılmaz, 2011). In the context of the current research, there were also studies in which the CSP was conducted only in the context of social studies teachers (Aykırı, 2017;Beldağ, Yaylacı, Gök and İpek, 2015;Bulut and Kara, 2012;Çetin and Sönmez, 2009;Gökçe, 2011;Kara, Altıntaş and Kaya, 2017;Kesten, Koçer and Egüz, 2014;Sönmez, 2010). These studies conducted with social studies teachers reported that prospective teachers gained achievements more in line with the aim and content of the course and contributed to the subjects such as "social skills development" (Sönmez, 2010), increased their sensitivity to social problems and contributed to their personal development (Gökçe, 2011), the participants generally had positive thoughts in terms of subjects covering the course aim and context (Çetin and Sönmez, 2009) and that the values gained in this process addressed the affective field and contributed to the internalization of these values and transformation into behavior with concrete practices (Kara, Altıntaş and Kaya, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Problems such as insensitivity and negative attitudes of the public, bureaucratic problems, negative attitudes and attitudes of the institution/organization authorities, difficulty of the target audience (patient, disabled, etc. ), the need to visually prove the effectiveness, transportation and meeting needs, identifying the target audience and activities (Aykırı, 2017), lack of interest in projects (Beldağ, Yaylacı, Gök and İpek, 2015), problems in organizing, and inability to continue the activities started in the course due to concerns about nationwide exams such as KPSS and ALES (Kesten, Koçer and Egüz, 2014) can be listed. In this study, the institution/place where the applications were made within the scope of the CSP course was placed at the center.…”
Section: Introductionmentioning
confidence: 99%